Peran Keluarga dalam Mencegah Perilaku Menyimpang (Studi Pada Remaja Pengguna Lem Ehabon di Kelurahan Karame Kecamatan Singkil) - Horman, Yuly Yanty; Mokalu, Benidicta; PURWANTO, ANTONIUS (Sam Ratulangi University, 2018)
The success of adolescents is determined how the role of the family to the child's growth anddevelopment. Families, especially parents, are the main educators and the first for children in the familyand in this family can be instilled attitudes that can affect the development of the next child. Adolescence isclosely related to juvenile delinquency. It was during this period that it was known as a full of energy,curious, not fully mature, vulnerable, brave, brave, highly emotive, always wanting to try, and not to be left2behind. At this time adolescents are the most vulnerable groups associated with drug abuse one of them isthe use of glue aibon (inhalen). The purpose of this study is to examine and reveal the Family Role inpreventing deviant behavior on Aibon user Tasks in Karame Sub-district of Kecamatan Singkil of Manado.The methodology used in this study used qualitative research with in-depth interview techniques.This study aims to explain and analyze the social interactions of adolescents, family roles and the role ofgovernment in preventing adolescent users glue aibon. The informants in this study are 11 people consistingof, Teen User 6 people, Parents 3 people, Village Head and from BNN North Sulawesi Province. Thisresearch was conducted from January 2018 in Karame Village, Singkil Sub-district, Manado City.Behavior is a person's behavior or action to inhale the scent of glue material usually used to glueor stick to a tire. Glue aibon is a drug inhalen (ngelem). This type of glue is often misused by teenagers tomake a hangover because this glue belongs to a dangerous addictive substance category. The theory usedin this research is the theory of sociology of deviant behavior is the theory of deferential association.From the results of in-depth interviews are known that the factors that encourage adolescents touse glue aibon the influence of friends of the same age, environment, family, and the availability andaffordability glue aibon. Families do not really care when their kids hang out with anyone their friends,even the ignorance of teenagers and even parents about the dangers of using glue aibon. Institutions dikaidand local governments often socialize about the dangers of glue aibon but not yet fully understood andunderstood by the community.This research suggests that families play an important role for the survival of their children suchas inculcating good values, establishing good communication, paying attention to every development andpaying more attention to who their children are. Teenagers should be aware that the use of glue aibonnegative impact both in terms of physical and psychological aspects. The related institutions must constantlysocialize the dangers of using glue aibon and other addictive substances to the community.Keywords: Youth, Family Role (Parents), Aibon ‘Glue